2020
DOI: 10.1371/journal.pone.0236153
|View full text |Cite
|
Sign up to set email alerts
|

Does mathematics training lead to better logical thinking and reasoning? A cross-sectional assessment from students to professors

Abstract: Mathematics is often promoted as endowing those who study it with transferable skills such as an ability to think logically and critically or to have improved investigative skills, resourcefulness and creativity in problem solving. However, there is scant evidence to back up such claims. This project tested participants with increasing levels of mathematics training on 11 well-studied rational and logical reasoning tasks aggregated from various psychological studies. These tasks, that included the Cognitive Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 25 publications
0
25
0
2
Order By: Relevance
“…The reasoning and argument indicators showed that the subject misunderstood the problem. Reasoning and argument indicators were correlated with critical thinking skills (Cresswell & Speelman, 2020;Palinussa, 2013;Su et al, 2016). It was because low essential skills of thinking impacted a person's capacity to interpret and argue based on the problems they face.…”
Section: Discussionmentioning
confidence: 99%
“…The reasoning and argument indicators showed that the subject misunderstood the problem. Reasoning and argument indicators were correlated with critical thinking skills (Cresswell & Speelman, 2020;Palinussa, 2013;Su et al, 2016). It was because low essential skills of thinking impacted a person's capacity to interpret and argue based on the problems they face.…”
Section: Discussionmentioning
confidence: 99%
“…They will become capable of implementing skills of mathematical discipline toward exercising logical thinking when the problems are solved by them. According to the study by Cresswell and Speelman (2020), the mind is disciplined by mathematical training, and it develops critical as well as logical reasoning along with problem-solving and analytical skills within the students. Most schools design the course of mathematics in a way that it forms deep analytical thought, creative thinking, mathematical fluency as well as understanding, and logical reasoning not in primary grades students but also in the students in secondary grades.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematics is one of the subjects that is useful for developing students' critical thinking skills [34][35][36][37][38] because it involves reasoning, making decisions, and solving problems. Mathematical critical thinking skills involve the process of thinking and integrating knowledge of mathematics to solve mathematical problems using mathematical reasoning and problem-solving strategies [35,39].…”
Section: Introductionmentioning
confidence: 99%